Research on Financial Risk Identification and Prevention Countermeasures for Green Transformation of Resource-Intensive Enterprises - Xue, Shuochen (Asia Pacific Economic and Management Review, 2026)
Against the backdrop of the in-depth advancement of the "Dual Carbon" strategic goals and ecological civilization construction, resource-intensive enterprises are confronted with an urgent demand for green transformation. From the perspective of accounting and financial management, this paper conducts a systematic study on the identification and prevention countermeasures of financial risks in the process of green transformation of resource-intensive enterprises. It is found that the financial risks of such enterprises in green transformation are mainly reflected in four aspects: insufficient capital supply and excessively high financing costs in the financing link; faulty investment decisions and lower-than-expected returns in the investment link; unbalanced cost control and tight cash flow in the operation and profit distribution link; as well as risks of adapting to policy adjustments and meeting environmental compliance standards in the policy compliance link. These risks arise from the combined effects of multiple factors, including the imbalance of internal financial management and control, the tightening of external environmental constraints, the inherent attribute restrictions of transformation, and the inadequacy of technical adaptation and internal control systems. In response to the above problems, this paper puts forward prevention countermeasures such as optimizing financing and investment management, strengthening the control of operation and profits, abiding by the bottom line of policy compliance, and constructing a comprehensive financial risk early warning system. The research shows that the financial risks of resource-intensive enterprises in green transformation are characterized by concealment, transmission and long-term nature, and it is necessary to build a systematic and full-process risk prevention and control system. This is to realize the coordinated development of ecological, economic and social benefits, and provide theoretical reference and practical guidance for enterprises to advance green transformation in a steady manner.